REVEALING THE COMPANY’S POSITIVE IMAGE THROUGH SUISTAINABILITY REPORT BASED ON GRI STANDARTS AND FINANCIAL PERFORMANCE IN THE AGRICULTURE, MINING AND BASIC INDUSTRY INDUSTRIES - Desy Ismah Anggraini; Pramandyah Fitah Kusuma; Rodhiyah Rodhiyah (SEAN Institute, 2023)
Environmental problems are currently receiving serious attention and issues related to the environment are becoming more sensitive, so that the government through UU No. 40 of 2007 the disclosure of social responsibility. In order to improve clarity and consistency in sustainability reports, the GRI Program was formed with three priority sector standards which will later become examples, namely companies engaged in the agriculture, fishing, oil and gas, and coal industries. The purpose of this study is to analyze the role of sustainability reports based on the GRI Standards which have three standard aspects, namely economic standards, environmental standards, and social standards that can reveal a company's financial performance. This study uses multiple linear regression analysis using data on the sustainability report and annual report for 2021. The results show that economic and social aspects affect financial performance while environmental aspects do not affect financial performance.